A Rapid Review on matrix rhythm therapy (Journal of Pharmaceutical Negative Results, 2022)
This brief study focuses on the effectiveness of Matrix rhythm therapy which exist as new development in the stream of physiotherapy used for the purpose of relieving pain, improves microcirculation, relaxation and increases oxygen supply of blood. A non-invasive method for gently releasing muscular tension and obtaining quick pain relief that can be used in conjunction with other forms of manual therapy or on its alone. A frequency range of 8-12 hz to stimulates the body’s natural self-healing powers storing good tissue resonance using a device by vibromassage method. The vibrating magneting field goes deep into the tissues via a reasonating head sending a phase synchronised mechanical vibration. It is used in conditions like chronic back pain, frozen shoulder, stroke, plantar fasciitis and lymphedema. In rehabilitation facilitate and compensatory education, clubs of sports, and neurological, orthopaedic, physiotherapy, and rehab centres, a new vibromassage application is being implemented.